Abundance of ACVR1B transcript is elevated during septic conditions: Perspectives obtained from a hands-on reductionist investigation - Preechanukul, Anucha; Yimthin, Thatcha; Tandhavanant, Sarunporn; Brummaier, Tobias; Chomkatekaew, Chalita; Das, Sukanta; Syed Ahamed Kabeer, Basirudeen; Toufiq, Mohammed; Rinchai, Darawan; West, T. Eoin; Chaussabel, Damien; Chantratita, Narisara; et al. (Frontiers in Immunology, 2023)
Sepsis is a complex heterogeneous condition, and the current lack of effective indicators of risks and outcomes hinders the improvement of its management. Using a reductionist approach leveraging publicly available transcriptomic data, we describe a knowledge gap for the role of ACVR1B (activin A receptor type 1B) in sepsis. ACVR1B, a member of the transforming growth factor-beta (TGF-beta) superfamily, was selected based on the following: 1) being induced upon in vitro exposure of neutrophils from healthy subjects with the serum of septic patients (GSE49755), and 2) the absence or minimal overlap between the ACVR1B literature and the sepsis, inflammation or neutrophil literature. Moreover, ACVR1B expression is upregulated in septic melioidosis, a widespread cause of fatal sepsis in the tropics, and associated with mortality in melioidosis patients. Key biological concepts extracted from a series of PubMed queries established indirect links between ACVR1B and “cancer”, “TGF-beta superfamily”, “cell proliferation”, “inhibitors of activin”, and “apoptosis”. We confirmed our observations by measuring ACVR1B transcript abundance in buffy coat samples obtained from healthy individuals (n=3) exposed to septic plasma (n = 26 melioidosis sepsis cases) ex vivo. Based on our re-investigation of publicly available transcriptomic data and newly generated ex vivo data, we provide perspective on the role of ACVR1B during sepsis. Additional experiments for addressing this knowledge gap are discussed.